The effects of high doses of nandrolone decanoate and exercise on prostate microvasculature of adult and older rats - Melo Neto, Joao Simao de; Gomes, Fabiana de Campos [UNESP]; Felipe Pinheiro, Patricia Fernanda [UNESP]; Pereira, Sergio [UNESP]; Scarano, Wellerson Rodrigo [UNESP]; Favaro, Wagner Jose; Domeniconi, Raquel Fantin [UNESP] (Elsevier B.V., 2015)
Aims: The present study aimed to investigate the effects of the interaction between the abusive use of nandrolone decanoate (ND) and physical activity on the prostate structure of adult and older rats. We evaluated whether the use of ND, associated or not with physical exercise during the post-pubertal stage, interferes with the morphophysiology of the prostate.Main methods: Fifty-six male Sprague-Dawley rats were divided into eight groups. The animals were treated for eight weeks and divided into sedentary and trained groups, with or without ND use. Four groups were sacrificed 48 h after the end of the eight week experiment (adult groups), and four other groups were sacrificed at 300 days of age (older groups). The prostate was collected and processed for stereological and histopathological analysis and for the expression of AQP1 and VEGF by the Western blotting technique.Key findings: Both ND and physical activity altered the ventral prostate structure of the rats; the AQP1 and VEGF expression increased in young animals subjected to physical exercise.Significance: Thus, it was concluded that the use of ND, associated or not with exercise during the post-pubertal stage, interferes with the morphophysiology of the prostate. (c) 2014 Elsevier Inc All rights reserved.
Keywords: Ventral prostate; VEGF; AQP1; Anabolic; Resistance physical exercise